2010
DOI: 10.1371/journal.pone.0011468
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Mutations Induce Mitochondrial Dysfunction, Apoptosis and Sarcopenia in Skeletal Muscle of Mitochondrial DNA Mutator Mice

Abstract: BackgroundAging results in a progressive loss of skeletal muscle, a condition known as sarcopenia. Mitochondrial DNA (mtDNA) mutations accumulate with aging in skeletal muscle and correlate with muscle loss, although no causal relationship has been established.Methodology/Principal FindingsWe investigated the relationship between mtDNA mutations and sarcopenia at the gene expression and biochemical levels using a mouse model that expresses a proofreading-deficient version (D257A) of the mitochondrial DNA Polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
203
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(223 citation statements)
references
References 85 publications
16
203
3
1
Order By: Relevance
“…It is well established that the massive free radical production in aging cells and organisms has been closely associated with higher rates of both DNA and RNA mutation (Robert et al 2010), confirming previous reports of an inverse association between DNA oxidation rates and longevity (Barja and Herrero et al 2000). It also has been demonstrated that mtDNA mutation impaired oxidative phosphorylation, without further free radical enhancement, leading to apoptosis of skeletal muscle cells and sarcopenia (Hiona et al 2010). By the same manner, detraining and sedentary behavior reduce mitochondrial biogenesis.…”
Section: Tac In Aging and Detraining: Is The Lack Of Exercise The Orisupporting
confidence: 63%
See 1 more Smart Citation
“…It is well established that the massive free radical production in aging cells and organisms has been closely associated with higher rates of both DNA and RNA mutation (Robert et al 2010), confirming previous reports of an inverse association between DNA oxidation rates and longevity (Barja and Herrero et al 2000). It also has been demonstrated that mtDNA mutation impaired oxidative phosphorylation, without further free radical enhancement, leading to apoptosis of skeletal muscle cells and sarcopenia (Hiona et al 2010). By the same manner, detraining and sedentary behavior reduce mitochondrial biogenesis.…”
Section: Tac In Aging and Detraining: Is The Lack Of Exercise The Orisupporting
confidence: 63%
“…By the same manner, detraining and sedentary behavior reduce mitochondrial biogenesis. Thus, the aging subject frequently has lower muscle mitochondrial density and many senescent mitochondria which are related to reduced vital capacity, decreased physical fitness and to an increased risk of chronic and metabolic diseases (Ferrari 2008;Figueiredo et al 2008;Hiona et al 2010;Jackson et al 2010). Therein, positive associations have been observed between oxygen free radicals and both systolic and diastolic blood pressure values, whereas the association between ROS and arterial stiffness was only observed among hypertensive men (Kruger et al 2012).…”
Section: Tac In Aging and Detraining: Is The Lack Of Exercise The Orimentioning
confidence: 99%
“…The importance of exonucleolytic proofreading during mtDNA replication is clear from the phenotype of mice lacking mitochondrial polymerase proofreading through mutation of POLG, which show early-onset of many age-related phenotypes (Trifunovic et al 2004). 7 Mice carrying high levels of mitochondrial DNA mutation show sarcopenia and mitochondrial dysfunction in skeletal muscle (Hiona et al 2010), although this can be blunted by endurance exercise (Safdar et al 2011). They also show an accelerated age-related loss of retinal function (Kong et al 2011).…”
Section: Mitochondrial Nucleasesmentioning
confidence: 99%
“…Upregulation of the apoptotic pathway has been identified in premature aging models including mice lacking the antioxidant enzyme copper/zinc‐dependent superoxide dismutase (CuZnSOD or Sod1) that exhibit accelerated sarcopenia (Jang et al ., 2010), as well as interleukin‐10‐deficient mice that exhibit extreme frailty (Walston et al ., 2008). Increased levels of DNA laddering and caspase‐3 activity have been observed in transgenic mice expressing defective mitochondrial polymerase (Hiona et al ., 2010). …”
Section: Introductionmentioning
confidence: 99%